Comparative Analysis Of Mahmudkhoja Behbudiy’s Work “A Brief History Of Islam” (Zien Journal of Social Sciences and Humanities, 2025)
This article analyzes the content, historical significance, and comparative aspects of Mahmudkhoja Behbudiy’s work “A Brief History of Islam.” The study examines the author’s religiouseducational approach, his method of presenting Islamic history in a simple and accessible language, as well as his innovative role in conveying religious history to the public on a scientific basis. Through comparative analysis, the article identifies the place of Behbudiy’s work in the Islamic thought of his time and highlights its methodological and conceptual differences from the writings of historians such as al-Tabari, Jurjani, Ibn al-Athir, and Ahmad Donish